Observations of planetary waves in the mesosphere-lower thermosphere during stratospheric warming events - N. H. Stray; Y. J. Orsolini; P. J. Espy; V. Limpasuvan; R. E. Hibbins (Atmospheric Chemistry and Physics, 2015)
This study investigates the effect of stratospheric sudden warmings (SSWs) on planetary wave (PW) activity in the mesosphere–lower thermosphere (MLT). PW activity near 95 km is derived from meteor wind data using a chain of eight SuperDARN radars at high northern latitudes that span longitudes from 150° W to 25° E and latitudes from 51 to 66° N. Zonal wave number 1 and 2 components were extracted from the meridional wind for the years 2000–2008. The observed wintertime PW activity shows common features associated with the stratospheric wind reversals and the accompanying stratospheric warming events. Onset dates for seven SSW events accompanied by an elevated stratopause (ES) were identified during this time period using the Specified Dynamics Whole Atmosphere Community Climate Model (SD-WACCM). For the seven events, a significant enhancement in wave number 1 and 2 PW amplitudes near 95 km was found to occur after the wind reversed at 50 km, with amplitudes maximizing approximately 5 days after the onset of the wind reversal. This PW enhancement in the MLT after the event was confirmed using SD-WACCM. When all cases of polar cap wind reversals at 50 km were considered, a significant, albeit moderate, correlation of 0.4 was found between PW amplitudes near 95 km and westward polar-cap stratospheric winds at 50 km, with the maximum correlation occurring ∼ 3 days after the maximum westward wind. These results indicate that the enhancement of PW amplitudes near 95 km is a common feature of SSWs irrespective of the strength of the wind reversal.